Erectile function after WST11 vascular-targeted photodynamic therapy for low-risk prostate cancer treatment - Samuel Chelly; Pierre Maulaz; Pierre Bigot; Abdel Rahmene Azzouzi; Souhil Lebdai (Asian Journal of Andrology, 2020)
Vascular-targeted photodynamic therapy (VTP) using padeliporfin is currently assessed as a low-risk prostate cancer (LRPCa) treatment. The aim of this study was to assess erectile function outcomes of VTP for LRPCa treatment. We prospectively included all patients treated with VTP for LRPCa. The primary endpoint was the post-treatment International Index of Erectile Function score (IIEF5 score) evolution (at 6 months, 12 months, and then every year for 5 years). Secondary endpoints were the need of erectile dysfunction (ED) treatment and its efficacy. Eighty-two men were included. The median follow-up was 68 (range: 6-89) months. There was a 3-point significant decrease in the median IIEF5 score between baseline and at 6 months post-VTP (23 [range: 1–25] vs 20 [range: 1–25], P = 0.005). There was a 1-point decrease at 1 year and 2 years post-VTP compared to baseline (22 [range: 2–25] and 22 [range: 0–25], P < 0.005). There was no significant difference at 3, 4, and 5 years compared to baseline. Twenty-seven (32.9%) patients received ED treatment: phosphodiesterase type-5 inhibitors (PDEI5; n = 18), intracavernous injections (ICI; n = 9), and intra-urethral gel (n = 1). The median IIEF5 score statistically significantly increased after ED treatment (7 [range: 0–24] vs 21 [range: 1–25], P < 0.001). ED treatment was efficient for 75% of the patients. There was no statistically significant difference between IIEF5 score at baseline and after ED treatment (P = 0.443). Forty-six patients were totally potent before VTP and among them, 13 needed ED treatment post-VTP with a success rate of 69.2%. VTP induced minimal changes in erectile function with a 3-point and a 1-point reduction in the IIEF5 score at 6 months and at 1 year, respectively. When required, ED treatment was efficient.